1996
DOI: 10.1002/(sici)1097-0185(199602)244:2<265::aid-ar14>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Relative frequency of a subclavian vs. a transverse cervical origin for the dorsal scapular artery in humans

Abstract: Background: The origin of the dorsal scapular artery to the rhomboid muscles in humans has been the subject of uncertainty. The present study sought to clarify which of its two most common sources (the transverse cervical artery or the subclavian artery) is the major source of the dorsal scapular artery. Methods: Gross anatomical dissection was used to visualize the origin and course of the dorsal scapular artery in human cadavers.Results: We found that the dorsal scapular artery typically arises from either o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 0 publications
3
19
0
Order By: Relevance
“…However, cadaveric studies of northern European and north American Caucasians have shown that the dorsal scapular artery (usually originating from the subclavian) has a particularly intimate relationship with the brachial plexus [4,7] at the level of the supraclavicular fossa (Fig. 1).…”
mentioning
confidence: 99%
“…However, cadaveric studies of northern European and north American Caucasians have shown that the dorsal scapular artery (usually originating from the subclavian) has a particularly intimate relationship with the brachial plexus [4,7] at the level of the supraclavicular fossa (Fig. 1).…”
mentioning
confidence: 99%
“…Cadaveric examination by Reiner and Kasser [9] showed that 75% of DSAs arose from the subclavian artery and 25% from the TCA. Subclavian origins were approximately equally divided between the second part (35.7%) and third part (38.9%).…”
Section: Discussionmentioning
confidence: 99%
“…When the dorsal scapular artery arises directly from the subclavian artery (31% of specimens, Chaijaroonkhanarak et al 2014;69%, Huelke 1958;75%, Reiner and Kasser 1996), it pierced the brachial plexus. When the dorsal scapular artery arose from the thyrocervical trunk, which is the other origin (23% of specimens, Reiner and Kasser 1996;30%, Huelke 1958;69%, Chaijaroonkhanarak et al 2014) the dorsal scapular artery passed over the brachial plexus and did not pierce between the nerves. The most common location of the dorsal scapular artery to pierce the brachial plexus is between the upper and middle trunks (46% of specimens, Huelke 1958; 63%, Chaijaroonkhanarak et al 2014;69%, Reiner and Kasser 1996).…”
Section: Variationsmentioning
confidence: 99%